Radionuclide distributions in Olympic Dam copper concentrates: The significance of minor hosts, incorporation mechanisms, and the role of mineral surfaces. (15th March 2020) - Rollog, Mark; Cook, Nigel J.; Guagliardo, Paul; Ehrig, Kathy; Kilburn, Matt
Highlights: Radionuclides (RNs) may be mapped at high resolution in mineral grains by nanoSIMS. RNs are found in apatite, fluorite, rutile, hematite, zircon, and REE minerals. High surface area minerals may host significant concentrations of RNs. Sulphuric acid leaching mobilises and relocates RNs, causing secular disequilibrium. Abstract: Some iron oxide-copper-gold (IOCG) deposits contain variable amounts of uranium. Developing mineral deportment models for the radiogenic isotopes resulting from decay of 238 U presents a singular technical challenge, as concentrations of 226 Ra, 210 Pb, and 210 Po fall far below the detection limits achievable for most in situ analytical methodologies. The nanoscale secondary ion mass spectrometry (nanoSIMS) platform combines low detection limits with sub-micron resolution, revealing previously unseen spatial distribution patterns of radionuclides (RNs) in (and on) particles of copper sulphide concentrates. Many potential host minerals for these radionuclides can be readily predicted based on chemical behaviour, periodic table trends, and published studies documenting likely host minerals. Using nanoSIMS data for ores and metallurgical products from the Olympic Dam IOCG deposit and associated processing facilities, we present compelling evidence for the ability of certain minerals within the copper concentrates to host daughter radionuclides derived from uranium decay. Many of these minerals had not traditionally been considered or previously documented as such. These include high-abundance minerals hosting low concentrations of radionuclides, and several relatively low abundance minerals exhibiting remarkable radionuclide enrichment. Rutile, fluorapatite, fluorite, hematite, zircon, covellite, and molybdenite are all proven to be minor hosts of at least some members of the 238 U decay chain, and are, collectively, important for establishing the overall RN budget. Surface effects are found to play a significant role, with elevated levels of 226 Ra and 210 Pb found on most available surfaces, irrespective of mineral, in acid-leached concentrate. Some rRNs, particularly 226 Ra and 210 Pb liberated from uranium minerals during sulphuric acid leaching, can become extensively redistributed throughout the concentrate, creating newly-formed RN hosts. This new mineralogical deportment information can be used in developing new flowsheets to enhance radionuclide removal without a corresponding loss of Cu. NanoSIMS has proven invaluable for elucidating the mineral-scale deportment of ultra-trace radionuclides throughout the processing circuit at Olympic Dam.